Web Brutalism: Assessing Usability of an Ugly Web - Palacios, Antonio (2022)
Brutalist websites are a contemporary trend that uses anti-aesthetic interface elements to create a high-impact visual product. Since the web is a communications product, this research sought to understand if the aesthetics of Brutalist sites overshadow their usability, defined as the ability of a user to effortlessly navigate through the contents of a digital interface to achieve a goal or retrieve information. Triangulation was applied to obtain a solid understanding of the problem. Consequently, three experiments were conducted on a Brutalist website using a group of thirty-one participants. First, Nielsen’s Attributes of Usability Questionnaire (NAU), a test that focuses on five key aspects of usability: learning, efficiency, memorisation, errors, and satisfaction. Second, Brooke’s System Usability Scale (SUS) test to gain deeper insight into the users’ perspective. Third, the Thinking Aloud (TA) protocol to obtain qualitative information to complement the first two experiments. After analysing the data of the NAU and SUS experiments, a numeric score was given to the perused website to objectively evaluate its usability and assign it to five categories, ranging from Deficient (E) to Excellent (A). Those results were complemented by the TA protocol. The findings highlight difficulties to retrieve information, navigation issues, and a lack of orientation. The use of an unconventional graphical user interface impacts the user experience. This study demonstrates that heuristics are necessary to develop robust interfaces and that deviating from these norms is detrimental to the user experience. The visual features of Brutalist websites, though striking, do not deliver a user-centred project.